T cell specific deletion of Casitas B lineage lymphoma-b reduces atherosclerosis, but increases plaque T cell infiltration and systemic T cell activation - Vos, Winnie G.; van Os, Bram W.; den Toom, Myrthe; Beckers, Linda; van Roomen, Cindy P.A.A.; van Tiel, Claudia M.; Mohapatra, Bhopal C.; Band, Hamid; Nitz, Katrin; Weber, Christian; Atzler, Dorothee; de Winther, Menno P.J.; et al. (Frontiers in Immunology, 2024)
Introduction Atherosclerosis is a lipid-driven inflammatory disease of the arterial wall, and the underlying cause of the majority of cardiovascular diseases. Recent advances in high-parametric immunophenotyping of immune cells indicate that T cells constitute the major leukocyte population in the atherosclerotic plaque. The E3 ubiquitin ligase Casitas B-lymphoma proto-oncogene-B (CBL-B) is a critical intracellular regulator that sets the threshold for T cell activation, making CBL-B a potential therapeutic target to modulate inflammation in atherosclerosis. We previously demonstrated that complete knock-out of CBL-B aggravated atherosclerosis in Apoe-/- mice, which was attributed to increased macrophage recruitment and increased CD8+ T cell activation in the plaque. Methods To further study the T cell specific role of CBL-B in atherosclerosis, Apoe-/- CD4creCblbfl/fl (Cbl-bcKO) mice and Apoe-/-CD4WTCblbfl/fl littermates (Cbl-bfl/fl) were fed a high cholesterol diet for ten weeks. Results Cbl-bcKO mice had smaller atherosclerotic lesions in the aortic arch and root compared to Cbl-bfl/fl, and a substantial increase in CD3+ T cells in the plaque. Collagen content in the plaque was decreased, while other plaque characteristics including plaque necrotic core, macrophage content, and smooth muscle cell content, remained unchanged. Mice lacking T cell CBL-B had a 1.4-fold increase in CD8+ T cells and a 1.8-fold increase in regulatory T cells in the spleen. Splenic CD4+ and CD8+ T cells had increased expression of C-X-C Motif Chemokine Receptor 3 (CXCR3) and interferon-γ (IFN-γ), indicating a T helper 1 (Th1)-like/effector CD8+ T cell-like phenotype. Conclusion In conclusion, Cbl-bcKO mice have reduced atherosclerosis but show increased T cell accumulation in the plaque accompanied by systemic T cell activation.